2019
DOI: 10.3389/fpsyt.2019.00104
|View full text |Cite
|
Sign up to set email alerts
|

Primary Cilia–An Underexplored Topic in Major Mental Illness

Abstract: Though much progress has been made in recent years towards understanding the function and physiology of primary cilia, they remain a somewhat elusive organelle. Some studies have explored the role of primary cilia in the developing nervous system, and their dysfunction has been linked with several neurosensory deficits. Yet, very little has been written on their potential role in psychiatric disorders. This article provides an overview of some of the functions of primary cilia in signalling pathways, and demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 177 publications
(184 reference statements)
2
9
0
Order By: Relevance
“…Although this gene has not been studied in the context of neuropsychiatric disorders, alterations in primary cilia structure have been implicated in reduced adult neurogenesis (Amador-Arjona et al, 2011) and poor novel object learning (Wang et al, 2011), and fewer primary cilia are observed in neurons from schizophrenic patients that were derived in vitro (Munoz-Estrada et al, 2018). In the context of our data, these studies provide a rationale for additional work examining the role of KIAA1009 in mediating altered cilia structure and function as it relates to stress-related psychopathology (Pruski and Lang, 2019). Increased NPY2R was also associated with AT (t = 1.93, p=0.0256) and is consistent with previous studies demonstrating the importance of the NPY system in mediating fear and anxiety responses (Roseboom et al, 2014).…”
Section: Discussionsupporting
confidence: 59%
“…Although this gene has not been studied in the context of neuropsychiatric disorders, alterations in primary cilia structure have been implicated in reduced adult neurogenesis (Amador-Arjona et al, 2011) and poor novel object learning (Wang et al, 2011), and fewer primary cilia are observed in neurons from schizophrenic patients that were derived in vitro (Munoz-Estrada et al, 2018). In the context of our data, these studies provide a rationale for additional work examining the role of KIAA1009 in mediating altered cilia structure and function as it relates to stress-related psychopathology (Pruski and Lang, 2019). Increased NPY2R was also associated with AT (t = 1.93, p=0.0256) and is consistent with previous studies demonstrating the importance of the NPY system in mediating fear and anxiety responses (Roseboom et al, 2014).…”
Section: Discussionsupporting
confidence: 59%
“…In addition, a recent study illustrated clearly that primary cilia formation was diminished in patients with schizophrenia and bipolar disorders (Muñoz-Estrada et al, 2017). Our data strengthen the case for both ciliary involvement in and the developmental nature of mental illness (Pruski and Lang, 2019).…”
Section: Discussionsupporting
confidence: 86%
“…Given the role of cilia in cell fate choice ( Kim et al, 2011 ; Li et al, 2011 ; Yeh et al, 2013 ), lack of ciliation could impact neuronal maturation and contribute to the development of the undifferentiated giant cells present in cortical tubers. Disorganized connectivity could also be a TSC-associated manifestation arising from alterations in cilia-dependent functions such as defective neuronal migration, polarization, or cortical lamination ( Park et al, 2018 ; Pruski and Lang, 2019 ; Sarkisian and Guadiana, 2015 ). Finally, given the role of cilia in the control of cell cycle and cell proliferation, altered cilia signaling might also have an impact in the transformation of the subependymal nodules into the low-grade subependymal giant cell astrocytomas (SEGAs) seen in the CNS of TSC patients ( Álvarez-Satta and Matheu, 2018 ; Chan et al, 2004 ; Ess et al, 2004 ; Sarkisian and Semple-Rowland, 2019 ).…”
Section: Discussionmentioning
confidence: 99%